FEATURES AND PROBLEMS OF POST-PRISON ADAPTATION OF JUVENILE CONVICTS: METHODS AND WAYS TO OVERCOME THEM - Nesterov Artyom Y. (Scientific Journal of Pedagogy and Economics, 2020)
The article analyzes the peculiarities of the adaptation of convicts, as well as identifies the main problems faced by juvenile convicts in the post-prison period. The author of the article will determine that the postprison adaptation of juvenile convicts released from the educational colony of the Federal Penitentiary Service of Russia must have, and has a preventive, rehabilitation and restorative character. It, in turn, should be focused on their cultural, moral, socio-economic, psychological, as well as the legal formation of personality in modern society. The scientific article presents the empirical material of the author’s sociological study conducted in two research stages: The first stage - the Main - 2014–2018 and the Second stage - Panel research - 2019–2020: 1) the problems faced by the convict during the period of serving the criminal punishment in the form of imprisonment and the post-prison period (from the personal experience of the convict); 2) the effectiveness (inefficiency) implemented by socio-pedagogical, socio-psychological, civil law, health measures in the institutions of the Federal Penitentiary Service of Russia; 3) adaptive penitentiary technologies implemented in the Federal Penitentiary Service of Russia in relation to minor convicts (2014–2020). Study sample: Convicts in FSI “СС-7” and FSI “СС-7” of the Federal Penitentiary Service of Russia in the Tula Region (n = 860 respondents), including the results of in-depth interviews of convicts (n = 34). Age of respondents: 18 - 65 years; Panel study conducted remotely in 2019–2020. Continuous questionnaire survey (n = 190), including the results of in-depth interviews of convicts (n = 23). Panel study conducted remotely in 2019– 2020. Continuous questionnaire survey (n = 223 convicted minors), including the results of an in-depth interview of convicts (n = 31). The age category of respondents is 21–35 years old / 35–50 years old; Panel study conducted remotely in 2019–2020. A continuous survey using the questionnaire survey method (n = 172), including the results of an in-depth interview of experts (n = 37). The study revealed - Twelve main problems that convicts in one way or another face in the post-prison period. Next, we conduct a ranking of identified problems by degree of importance, affecting the negative component of the convict in a given period, which forms the main trajectory of the social adaptation of the convict in modern Russian society. So, according to the author, the totality of all the main problems that juvenile convicts face in the post-prison period, one way or another, significantly complicates the adequate process of social adaptation of the convict and leads to the fact that the teenager, having criminal experience, and also disappointed in life, repeatedly involved in criminal activity, which will directly lead him back to prison. Also, based on an analysis of the positive practices for preparing convicts for release implemented in the penitentiary institutions of the Federal Penitentiary Service of Russia, it is possible to clearly establish the approximate composition of the subjects of social adaptation of convicts in the post-prison period. These entities may be recommended by the Federal Executive Body (the Ministry of Justice of the Russian Federation) to implement complex issues related to the rehabilitation of juvenile convicts. Based on a sociological study, the author develops the main ways and methods that focus on the successful social adaptation of prisoners in the post-prison period. The main conclusions of the study are formulated, which are as follows: 1) The post-penitentiary adaptation of a convict who has been released from FSI “EC” in the Federal Penitentiary Service of Russia represents a whole complex of life tasks that the released person will have to solve independently; 2) In some cases, to solve these problems it is necessary to “start life anew” - first of all, to acquire a profession; 3) Rebuild the familiar “scenario” of deviant behavior in relation to others and the system of basic values